Synthesis and Characterization of High Molecular Weight Chitosan, and Antioxidant Activity of Its Chitosan Oligosaccharide Encapsulation (Journal of Nepal Chemical Society, 2021)
High molecular weight nanocrystalline chitosan (HMWNC)with Mw of 350 kDa and 66.92% DDA was prepared by alkaline N-deacetylation of chitin that was abundantly obtained after demineralization and deproteinization of pulverized crab shells, and commercially available chitosan oligosaccharide (COS) with average Mw< 3000 Da and 87% DDA was encapsulated with HMWNC. The encapsulation of COS as a pharmaceutical ingredient into HMWC was hypothesized to enhance the bioavailability of COS in target cells. The HMWNC encapsulated chitosan oligosaccharide (COS-HMWNC) showed in vitro antioxidant activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals (IC50 = 512.6±14.4 μg/mL) while others showed less than 50% inhibition at 1000 μg/mL. The lower the molecular weight of chitosan, the higher was the antioxidant activity. The study showed that the encapsulation of COS molecules in HMWNCcould be used as a simple and effective way of enhancing the antioxidant activity of COS.